The Use of Song Lyrics to Analyze Figurative Language Style - Andreas Heri Kurniawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The purpose of this research is to describe the types of figurative language found in Adele's songs in album 30. The research methodology used is literature study with a qualitative descriptive approach. The results show that there are several types of figurative language in the lyrics of these songs, including symbolic (36%), personification (9%), metaphor (4.5%), simile (18%), hyperbole (4.5%), and allegory (28%). Thus, it can be concluded that the most used figurative language in the album is the symbolic type.